Croatian and Irish public libraries on Facebook - Hebrang Grgić, Ivana (Array, 2012)
Since its launch in 2004, Facebook has become one of the world’s most popular social networking sites. Its usage has increased significantly – that is the reason why libraries often use the network in promoting their activities. In the paper a short literature review is given (e. g. articles written by Jacobson (2011) ; Bencec (2011) and some others). After the review, results of a study of Croatian and Irish public libraries on Facebook are presented and conclusions are made. Facebook pages of all Croatian and Irish libraries are analyzed showing the main trends in using Facebook as well as libraries’ interaction with their users (fans). The results will show libraries’ and fans’ activities and will indicate what public libraries in both countries could do to enhance library promotion on Facebook.